Influence of age, qualification and period of annual cycle on the indexes of physical preparedness of biathlonists 14-17 years - Tkachenko V.B (Kharkov National Pedagogical University, 2010)
The system of tests is specified for a stage control of physical preparedness of biathlonists. The rates of changes of their indexes physical preparedness are probed on the stages of circannual cycle. Quantitative and high-quality indexes are studied for different age-dependent and qualifying groups. Influence of age is analysed, qualification and period of circannual cycle on physical preparedness of biathlonists 14-17 years. It enables to define their contribution to the change of indexes physical pre